DEVELOPMENT OF ENRICHED VIRTUAL CLASSROOM WITH PEDATI IN CONSTRUCTION COST ESTIMATE COURSE - Riza Nur Dwi Lutfiana; Dika Arya Yasa; Eveline Siregar (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
This study aims to develop designs and learning products for the Enriched Virtual Classroom using PEDATI in building construction planning. Enriched Virtual Classroom belongs to blended learning. This learning model is one of the models where the learning process is played with technology and face-to-face learning is only an additional supplement if needed. The development procedure uses the ADDIE model which is integrated with the PEDATI model at the learning design preparation stage. The components and indicators for the expert review of the instrument were prepared based on the standard components and indicators of the "Network-Based Learning Evaluation Instrument" developed by Hadiansyah, et al. in 2018. Instruments will be given to learning design experts in terms of five aspects, namely subject identity, clarity of learning objectives, the relevance of learning strategies to learning objectives, the relevance of evaluation to learning objectives as well as language and communication. The results of the evaluation use the scoring from the expert review by using proportions. The percentages obtained were 94.78% from instructional design experts, 95.71% from media experts, and 90.83% from instructional design experts.